Políticas de recursos humanos, do discurso oficial à prática : estudo realizado na administração direta do estado do Espírito Santo - Barroso, Dicleia Silva (1995)
The distance between the official discourse and the practice of the policy of Human Recourses defined for the \/vorkers of the Direct Administration of the Executive of Espirito Santo State in the period of 1971/1991, in this case study, was analysed having as conceptual base the theory of Public Policy analyse and Human Recourses. The programmed guidelines and the implemented actions were verified, making use of official documentation: plans of the governments, legislative dispatches, Laws, Decrets and other documentation, covering five different períods of government, reaching historical space of twenty years of the state Public Administration, embodying part of the periods called. 'Authorative Military Regime', 'Political opening' and 'New Republic'. In order to show important aspects and to obtain more precise description of the situation in study, field research was made, making use of the semi-structered interview, as instrument. Public managers and assessors were selected and interviewed, as well secretaries of state that acted in the scenery under investigation. In the periods of 1971/1991, the proposed guidelines followed rational procedures and the actions were implemented in na isolated way, going away from the proposed directrixes planned. The distance between the discourse and its practice is even considered as a natural procedure, whereas this research penneated five periods of government, whose politic sceneries were well different from each other, however the pratice used by several governors and public administrators, in relation to the Public Administration, and specially to the treatment given to Human Resources, was developed with the same disregard. Wherefore it is infered that in the period going from 1971 to 1991. The guidelines of the policy of Human Resources for the workers of the Direct Administration of the Executive of Espirito Santo State stayed only in the rethoric of the Governamental discourse, and, at any moment into the practice, they were implemented at the governamental levei.